Evaluation of Sales Patterns of Poultry Antibiotics and Vitamins in The Veterinary Drug Industry: Implications for Farm Health and Sustainability - Suganda; R. Afnan; Jakaria (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2025)
The growing chicken population in Indonesia reflects the expanding poultry farming industry. To maintain chicken health and treat diseases, vitamins and antibiotics are commonly used, with guidelines for their use changing over time. To understand usage trends, data from PT Tekad Mandiri Citra (TMC) in Bandung is needed. This study evaluates the sales patterns of poultry antibiotics and vitamins in the veterinary drug industry between 2020 and 2022, with a focus on farm health and sustainability. Additionally, a SWOT analysis will be used to replace colistin antibiotics, based on changes to the Minister of Agriculture Regulation No. 14 of 2017. Data were processed using Microsoft Excel 2019 for descriptive analysis. The results show that 79% of broiler farms use antibiotics, and 81% use vitamins. In 2022, the most common antibiotics were from the fluoroquinolone group (34%), and the most used vitamins were from the miscellaneous group (35%). The SWOT analysis for 2021-2022 indicates that replacing colistin products has been successful.